Socio-economic reintegration after medico-surgical management of obstetric fistula (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To study the socio-economic reintegration of victims of obstetric fistula after their recovery.Methods: Prospective and analytical cohort studyResults: The average age of women with obstetric fistula was 35.92 ± 9.80 years. 85.45% were housewives, 92.73% were out of school and 85.45% lived in rural areas. In about 43.64% of cases, obstetric fistula occurred in the first two pregnancies. The average age of fistula was 7.6 years with extremes of 2 months to 32 years. The average duration of labor was 53.29, resulting in caesarean delivery in 58% of cases and death of the newborn in 80% of cases. Marital status changed in 14% of cases after healing. Before surgery, 87% had stopped all economic activity, 76.36% did not participate in social events and 52.73% of cases had no regular sexual activity. After surgery, patients participated in all community celebrations in 91.18% of cases; there was sexual intercourse in 52.94% of cases and 14.71% of cases had returned to workConclusions: In order to ensure the restoration of a woman with dignity, medico-surgical management must be combined with social and economic support.